1993
DOI: 10.1111/j.1151-2916.1993.tb05308.x
|View full text |Cite
|
Sign up to set email alerts
|

Highly Reactive β‐Dicalcium Silicate: V, Influence of Specific Surface Area on Hydration

Abstract: The hydration of p-C,S prepared from hillebrandite [Ca,(SiO,)(OH),] and having specific surface areas of 6.8, 5.5, and 3.1 mz/g was investigated. Different specific areas were obtained by varying the dissociation temperature of hillebrandite. In addition, the hydration of $-C,S synthesized from high-temperature solid-state reaction was also studied as a comparison. The specific surface area exerts a strong influence on the hydration rate, which increases as the surface area increases. The degree of influence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…In general, the two types of fibers exhibited high level of dispersibility with minor quantities of aggregation, which was favorable to fabricate composites as reinforcement reagent. According to the previous studies by Sasaki et al, 26 ␤-Ca 2 SiO 4 fibers obtained from Ca 2 (SiO 3 )(OH) 2 maintained needle morphology when the heat-treatment temperature increased from 600 to 1100 • C. Our results confirmed this observation and suggested that ␤-Ca 2 SiO 4 fibers possessed excellent morphological stability during the heating process. (Fig.…”
Section: Soaking In Simulated Body Fluidsupporting
confidence: 94%
“…In general, the two types of fibers exhibited high level of dispersibility with minor quantities of aggregation, which was favorable to fabricate composites as reinforcement reagent. According to the previous studies by Sasaki et al, 26 ␤-Ca 2 SiO 4 fibers obtained from Ca 2 (SiO 3 )(OH) 2 maintained needle morphology when the heat-treatment temperature increased from 600 to 1100 • C. Our results confirmed this observation and suggested that ␤-Ca 2 SiO 4 fibers possessed excellent morphological stability during the heating process. (Fig.…”
Section: Soaking In Simulated Body Fluidsupporting
confidence: 94%
“…13,14 Traditionally, dicalcium silicate (Ca 2 SiO 4 ) is an important constituent in Portland cement, refractories and heat-resistant coatings. [15][16][17][18] Recent studies have shown that Ca 2 SiO 4 has the potential to be used as biomaterials. Liu et al 19 prepared Ca 2 SiO 4 coatings on the Ti alloys and a bonelike carbonated hydroxyapatite (CHA) layer formed on the surface of the coatings when soaked in SBF for 2 days.…”
Section: Introductionmentioning
confidence: 99%
“…The specific surface area affects the hydration reaction mechanism. In the case of specific areas of 5.5 m 2 /g or less, the reaction changes from a chemical reaction to a diffusion-controlled one [22]. The hydration rate of β -C 2 S enhances with raising curing temperature of hydration [23].…”
Section: Introductionmentioning
confidence: 99%